Early Alert of Biological Risk in a Coastal Lagoon Through eDNA Metabarcoding - Suarez-Menendez, Marcos; Planes, Serge; Garcia-Vazquez, Eva; Ardura, Alba (Frontiers in Ecology and Evolution, 2020)
Mediterranean coastal lagoons are environmentally important ecosystems whose conservation has been challenged due to anthropogenic impacts that promoted the expansion of non-indigenous and, sometimes, invasive species. Therefore, it is crucial to inventory biodiversity in these areas for the development of strategies of conservation and management. Classic methods used for biodiversity surveys and detection of non-native species may be unsuccessful for the detection and identification of species in early development stages, cryptic, microscopic, elusive and new coming species at low population density. The development of metabarcoding techniques in the last decade offers new opportunities for reliable biodiversity surveillance and facilitates early detection of nuisance species. The objective of this study was to analyse the species occurring in the protected coastal lagoon Canet-Saint Nazaire using a short and easy sampling protocol based on water samples and environmental DNA (eDNA) metabarcoding with a single barcode (COI gene). Two invasive species (Polydora cornuta and Acartia tonsa), two polychaetes bioindicators of pollution (Hediste diversicolor and Capitella capitata), and one alga that produces harmful algal blooms were detected from only six litres of water, pointing at lagoon’s environmental degradation despite its protection status. The results demonstrate the importance of COI as asingle barcode together with eDNA as an ecological warning system and suggest the need for environmental restoration in this lagoon.